MON-372 Asymptomatic Pheochromocytoma Masquerading as Right Upper Quadrant Abdominal Mass - Boddhula, Satish (J Endocr Soc, 2019)
Introduction: Pheochromocytomas (PCCs) are rare catecholamine-producing neuroendocrine tumors, mostly arising from the adrenal medulla (85%). We present an interesting case of a young woman with developmental delay who was diagnosed with pheochromocytoma after presenting with abdominal distention as the only initial complaint. Case presentation: A 44-year-old non-communicative Caucasian female with h/o severe developmental delay and seizure disorder presented to clinic with her caregiver for significant abdominal distention that developed over the last few days. On examination, abdomen was distended and firm to palpation. Abdominal ultrasound revealed 10.1 x 8.6 x 6.6 cm heterogenous mass in the right upper quadrant (RUQ), abutting and possibly contiguous with the liver. MRI abdomen revealed heterogenous mass originating from the caudate lobe measuring 8.5 x 6 x 12 cm. However, during CT guided biopsy, a large mass just right and anterior to the vertebral column and posterior to the liver raising suspicion for renal origin of the mass. Pressure was applied over the biopsy site to stop bleeding after obtaining core biopsies. She immediately developed hypertension with BP 240/164 mm hg, HR 123 bpm, RR 19, temperature 38.3°C concerning for catecholamine-secreting tumor. She became hypoxic and stat CXR revealed flash pulmonary edema. She was intubated for acute hypoxic respiratory failure. EKG showed sinus tachycardia. Her BP decreased to 150/70, HR 100/min after giving her IV labetalol. Labs showed serum sodium 141, potassium 4.9, bicarb 15, AG 15, hemoglobin 17.6, lactic acidosis of 6.1, AST 4670 U/L (N: 14-36), ALT 2955 U/L (N: 9-52), creatinine 2.1 mg/dl, troponin 0.61 ng/ml (Ref: < 0.05 ng/mL) and CK 2351 U/L (N: 30-175). Transthoracic echocardiogram showed normal findings. Serum metanephrines revealed elevated total metanephrines (26 nmol/L), norepinephrine (49 nmol/L) and 24-hour urine catecholamines: total metanephrines level 33635 mcg/24 h and normetanephrines 17850. She improved clinically, was extubated and discharged on phenoxybenzamine and metoprolol. She underwent surgical resection of the abdominal mass with no postoperative complications and the biopsy report confirmed PCC. Discussion: In a young patient presenting with RUQ abdominal mass, it is imperative to rule out secondary causes such as adrenal tumors (PCC), especially in patients with limited history. Initial biochemical testing to exclude conditions like PCC should always be considered prior to invasive procedures involving masses close to the adrenal gland, as manipulation or biopsy of a pheochromocytoma may have dreadful consequences. Our case illustrates the necessity of maintaining a broad differential when evaluating cases with RUQ abdominal masses which are close to the adrenal gland, and to consider other modalities of testing depending on the index of suspicion prior to biopsy of the mass.